Case Report: A neurolinguistic and neuroimaging study on a Chinese follow-up case with logopenic-variant of primary progressive aphasia - Huang, Binyao; Wang, Xiaolu; Jiang, Biao; Kong, Linlin; Hou, Haifeng; Zhou, Jiong (Frontiers in Neurology, 2022)
Primary progressive aphasia, typically resulting from a neurodegenerative disease, is characterized by a progressive loss of specific language functions while other cognitive domains are relatively unaffected. Currently, there are three distinct subtypes of it: semantic variant, non-fluent/agrammatic variant, and logopenic variant. The logopenic variant, characterized by impairments of word retrieval and sentence repetition, is the most recently described variant and remains less understood than other variants due to a comparatively small number of case studies and lack of investigations with a thorough specification. To fill up this gap, we report a 2-year follow-up case study of a 74-year-old Chinese female patient with logopenic variant of primary progressive aphasia, including its neurolinguistic study, magnetic resonance imaging (MRI), and 11C-Pittsburgh compound B-Positron emission tomography imaging analyses, as well as gene sequencing. This case confirms that, in addition to word-finding and sentence repetition difficulties, the logopenic variant may also present with mild auditory comprehension and naming deficits, which are associated with impaired access to lexical representations. The observation of clinical treatment suggests adequate efficacy of Memantine Hydrochloride Tablet and Rivastigmine Transdermal Patch in slowing down the cognitive deterioration of this patient, except for a pronounced decline in repetition and calculation. By exploring this case, we can gain a deeper understanding of Chinese logopenic variant of primary progressive aphasia.